Bibliography of Law and Economics
XIII, 667 p.
Keywords: Law and economics can be considered as the most exciting development in legal scholarship in recent decades. This volume is the first all-encompassing bibliography in this area. It lists approximately 7000 publications, covering the whole area of law and economics, including `old' law and economics (topics such as antitrust law, labor law, tax law, social security, economic regulation, etc.) as well as `new' law and economics with such topics as tort law, contract law, family law, procedure, criminal law, etc.). The volume also includes the literature on the philosophical foundations and the fundamental concepts of the approach. Part Two gives a special survey of law and economics publications in Europe, written in other languages than English. The Bibliography of Law and Economics is an invaluable reference work for students, scholars, lawyers, economists and other people interested in this field.